2011
DOI: 10.1093/annonc/mdr470
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up with CA125 after primary therapy of advanced ovarian cancer: in favor of continuing to prescribe CA125 during follow-up

Abstract: Serum cancer antigen 125 (CA125) is widely used in ovarian cancer to monitor the effectiveness of therapy both in first line and recurrence. It is also widely used during follow-up, where it is able to identify a percentage of patients with asymptomatic recurrence. Although a recent Medical Research Council (UK)/European Organisation for Research and Treatment of Cancer trial has demonstrated that early chemotherapy in asymptomatic patients based only on CA125 increase does not prolong survival, we still belie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 30 publications
1
25
0
1
Order By: Relevance
“…Serum cancer antigen 125 level also has significant correlation with tumor stage, grade, and histologic type, making it a useful prognostic factor in epithelial ovarian cancer (25, 26). It is also a widely used monitoring tool for assessing the effectiveness of therapy and asymptomatic recurrence rates at follow-up (27). Other type of cancers also show abnormal genetic/epigenetic status.…”
Section: Gynecologic Cancermentioning
confidence: 99%
“…Serum cancer antigen 125 level also has significant correlation with tumor stage, grade, and histologic type, making it a useful prognostic factor in epithelial ovarian cancer (25, 26). It is also a widely used monitoring tool for assessing the effectiveness of therapy and asymptomatic recurrence rates at follow-up (27). Other type of cancers also show abnormal genetic/epigenetic status.…”
Section: Gynecologic Cancermentioning
confidence: 99%
“…Because of the vague symptomatic progression of the disease, most patients present at advanced stages (III–IV) and often recur after primary cytoreductive surgery and platinum-based chemotherapy, yielding a dismal 5-y survival rate of 27% (1,2). High-grade serous ovarian cancer (HGSOC) comprises the major malignant histotype (70%) of epithelial ovarian cancers and bears a molecular signature in the overexpression of MUC16/cancer antigen 125 (CA125), a serum biomarker for ovarian cancer (3). Indeed, among epithelial ovarian cancers, the frequency of CA125 positivity is higher in serous histotypes than in mucinous or clear cell disease (4).…”
mentioning
confidence: 99%
“…In recurrent HGSOC, the elevation in serum CA125 levels precedes radiologic detection by 3 mo and predates the clinical presentation of symptoms and diagnosis by a median lag time of 5 mo (3). However, elevated serum CA125 levels alone do not qualify as a criterion to initiate treatment in the absence of radiologic evidence of recurrent disease.…”
mentioning
confidence: 99%
“…Treatments in both groups according to standard local practice did not include SCS, but only used various platinum combinations. Earliest detection of recurrence-even biochemical evidence with positron emission tomography-computed tomography (PET/CT) or other biomarkerscould be useful for increasing the success rate of SCS considering that isolated or localized disease might be an important predictive factor of complete cytoreduction and improved survival [66]. Tanner et al showed that detection of asymptomatic recurrences by routine surveillance testing was associated with a high likelihood of optimal SCS in operative candidates, and extended OS in platinum-sensitive ROC although it remained to be prospectively explored [25,67].…”
Section: Timing Of Surgical Cytoreduction and Surveillancementioning
confidence: 99%